Pengaruh Online Customer Review dan Rating Terhadap Keputusan Pembelian Produk Halal Melalui Marketplace: Studi Kasus pada Mahasiswa Fakultas Syariah IAI-Nasional Laa Roiba Bogor - Evi Novita; Rio Kartika; Rintari Anis Fadilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Market places are an alternative for carrying out buying and selling activities easily because they can be done online. This research aims to determine the partial and simultaneous influence of Online Customer Reviews and Ratings on decisions to purchase halal products through the Marketplace. The population in this study were all students at the Sharia Faculty of IAI-National Laa Roiba Bogor and the samples used were based on the Tabachic & Fidell approach, the number of samples used was 35 samples. The results of the analysis show that partially online customer reviews have a significant positive effect and ratings do not have a significant effect on purchasing decisions. Simultaneously, online customer reviews and ratings have a significant influence on purchasing decisions.